Combined Application of Coagulation/Flocculation/Sedimentation and Membrane Separation for the Treatment of Laundry Wastewater - Camila O. C. Nascimento; Márcia T. Veit; Soraya M. Palácio; Gilberto C. Gonçalves; Márcia R. Fagundes-Klen (International Journal of Chemical Engineering)
The wastewater from industrial laundries has a high quantity of contaminants from the washing process, as well as chemical additives. Aiming at the treatment of this type of wastewater, the present study evaluated the performance of a combined coagulation/flocculation/sedimentation process (C/F/S) and membrane separation to treat laundry wastewater in relation to physicochemical parameters of water quality. For this purpose, a Doehlert experimental design was applied to the C/F/S step using the natural coagulant Tanfloc POP® with maximum color and turbidity removal efficiency obtained of 80.27% and 86.50%, respectively, under conditions of pH of 6.4 and a coagulant concentration of 110 mg·L−1. The supernatant from the C/F/S step was used in the sequential microfiltration (MF) and ultrafiltration (UF) experiments. The maximum values of color, total nitrogen, dissolved solids, and turbidity removal were similar to MF and UF membranes at transmembrane pressure of 1.4 bar, with the greatest flow of permeates (92.2 L·h−1·m−2) presented by the MF membrane at 1.4 bar. The total efficiency of the combined C/F/S-MF process indicated the quality of the treated wastewater since it reduced 98.4% of the color, 99.1% of turbidity, 71.7% of the surfactants, and more than 55% of the total dissolved solids (TDS), chemical oxygen demand (COD), and total organic carbon (TOC) from the industrial laundry wastewater. This study showed that the C/F/S-MF combined process could be an efficient treatment of laundry wastewater.